Implementation of an Education Empowerment Team to Promote Education-Focused Conversations in a Student-Run Free Clinic: A Reproducible Model - Jager, Shannon; Hentz, Emily; Pairitz, MacKenzie; Jansen, Shae; Sevilla-Martir, Javier (Journal of Student-Run Clinics, 2021)
Lack of time dedicated to patient education is a barrier to motivational, empathetic conversations in the setting of high patient volume at the Indiana University Student Outreach Clinic (IUSOC). The Education Empowerment Team (EET) was created to: (1) empower patients through educational conversations and (2) empower a cohort of graduate and health professional students to grow in the skills of motivational interviewing (MI) and patient education. The purpose of this study is to detail the EET implementation model and evaluate the successes and barriers encountered by team members during its first three months of implementation. Fifteen EET members were selected and completed three training sessions. A survey was dispersed to members of the EET after three months of implementation. Thematic analysis of the team’s qualitative perception of their role, as well as quantitative evaluation of encountered barriers and training session utilization was completed. McNemar’s test was implemented to determine significance. EET members found the MI pre-clinical training to be most utilized (p=0.02) and requested a second, ‘refresher’ MI training later in the year, as well as role-play training scenarios. Members found the public setting of EET encounters to be the largest barrier to effective patient-volunteer relationships. The EET was successfully implemented at the IUSOC from January to March 2020 when COVID-19 restrictions forced clinic closure. The shortened duration of the EET was the largest limitation of the study; yet, the reproducible EET implementation model serves as an effective starting point for the implementation of education-focused teams at student-run free clinics. Future steps involve modifying the EET model, expanding interdisciplinary heterogeneity of the team, and evaluating the impact of EET on patient health outcomes objectively by disease progress and subjectively by patients’ assessments.